Social Institutions of Muslims During The Time of Utsman and Ali - Taslim Batubara; Ilhamzah Ilhamzah (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2024)
This article aims to examine the social institutions of the Islamic community during the time of Uthman ibn Affan and Ali ibn Abi Talib. Uthman ibn Affan and Ali ibn Abi Talib were among the closest companions of Prophet Muhammad (PBUH) who belonged to the group of Assabiqunal Awwalun. During their leadership, the condition of social institutions within the Islamic community was already in disarray. Institutions themselves are interpreted as formal social behavior systems as well as customs and norms regulating human behavior in society. This article employs historical research methodology with four stages: heuristic, criticism, interpretation, and historiography. The data collection technique involves library research on relevant sources. The research findings indicate: (1) in the early days of his rule, Uthman still inherited the state authority that was previously high during Umar's rule. However, due to his advanced age, the management of the state was mostly handled by his closest relatives. However, the allegations of nepotism leveled against him were not proven true; (2) during Ali's leadership, the condition of Islamic community institutions became even more chaotic. Ali inherited a chaotic government from the time of Uthman, leading to unavoidable civil wars during his rule.